2016
DOI: 10.1039/c6sm00456c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic self-organization of microwell-aggregated cellular mixtures

Abstract: Cells with different cohesive properties self-assemble in a spatiotemporal and context-dependent manner. Previous studies on cell self-organization mainly focused on the spontaneous structural development within a short period of time during which the cell numbers remained constant. However the effect of cell proliferation over time on the self-organization of cells is largely unexplored. Here, we studied the spatiotemporal dynamics of self-organization of a co-culture of MDA-MB-231 and MCF10A cells seeded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…There is an emerging consensus [9][10][11][12][13] that adhesive molecules help to regulate cortical acto-myosin, which can strongly impact cell sorting. However, it remains controversial whether differential adhesion or differential cortical tension alone is sufficient to generate the level of cell sorting and compartmentalization observed in embryos and cell culture systems [14][15][16][17][18][19][20]. Several experiments have suggested that additional processes such as specialized cell-cell signaling [16] or cellular jamming [17] enhance or disrupt sorting in living tissues.…”
mentioning
confidence: 99%
“…There is an emerging consensus [9][10][11][12][13] that adhesive molecules help to regulate cortical acto-myosin, which can strongly impact cell sorting. However, it remains controversial whether differential adhesion or differential cortical tension alone is sufficient to generate the level of cell sorting and compartmentalization observed in embryos and cell culture systems [14][15][16][17][18][19][20]. Several experiments have suggested that additional processes such as specialized cell-cell signaling [16] or cellular jamming [17] enhance or disrupt sorting in living tissues.…”
mentioning
confidence: 99%
“…The results of the previous section demonstrate several advantages provided by our computational 4D-OCM imaging methods. Micrometer-scale details of both spheroid and collagen structure were observed over a large mm 3 scale volumetric field-of-view using only native scattering contrast. Rapid volumetric image acquisition (on the order of 10-15 seconds per volume, as detailed in the Methods) enabled the measurement of temporal fluctuations in the backscattered optical signals from cells, and these fluctuations were successfully exploited to enable the segmentation of cells from the surrounding collagen.…”
Section: Discussionmentioning
confidence: 99%
“…All OCT image reconstruction and subsequent image processing was performed in MATLAB R2018a. the MATLAB function imresize3 to yield a final voxel size of (1.88 μm) 3 and (2.34 μm) 3 for images of monoculture spheroids and co-culture spheroids, respectively. This down-sampling was used in order to perform smoothing and reduce computational load.…”
Section: Oct Image Reconstructionmentioning
confidence: 99%
“…Another category of samples for which observation chambers need to be designed and optimized are 3D multicellular aggregates. Proposed as in vitro tumour models 30 years ago 21 , they are now the subject of renewed interest because of the advances in optical sectioning microscopy 22 , the development of microfluidics strategies to produce them in a controlled fashion 23 24 25 , and the necessity for pharmaceutical and cosmetic companies to reduce animal testing for toxicity assays 26 . Initially restricted to the field of cancer biology 21 , the 3D multicellular aggregates have now numerous variants, such as embryoid bodies, organoids, neurospheres 27 28 29 30 31 .…”
mentioning
confidence: 99%